2012
DOI: 10.1016/j.socscimed.2012.04.023
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about the experience of age related macular degeneration? A systematic review and meta-synthesis of qualitative research

Abstract: Age Related Macular Degeneration (AMD) is the leading cause of registerable blindness with a high medical and societal cost burden. Much of the research examining experiences of living with AMD has been conducted independently with small sample sizes and has failed to impact on practice. Meta-synthesis of qualitative research can improve the understanding of the experience of living with AMD by drawing together findings of qualitative studies. This article presents a systematic review and meta-synthesis of qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 58 publications
1
68
1
2
Order By: Relevance
“…Previous literature on this topic is very limited and inconclusive about the frequency of depression in patients at different anti-VEGF treatment stages (9,22,28,34). One possible hypothesis to explain why depression is higher in patients at early stages of treatment is the fact of AMD is 10 often seen as a threatening condition that entails further blindness (50). Patients recently diagnosed with wAMD can therefore have that expectation of going blind.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature on this topic is very limited and inconclusive about the frequency of depression in patients at different anti-VEGF treatment stages (9,22,28,34). One possible hypothesis to explain why depression is higher in patients at early stages of treatment is the fact of AMD is 10 often seen as a threatening condition that entails further blindness (50). Patients recently diagnosed with wAMD can therefore have that expectation of going blind.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is acknowledged that restrictions in journal word limits might cause problems for authors in terms of providing methodological or analytical details (Garip & Yardley, 2011;Walsh & Downe, 2005). Appraisal was not undertaken to exclude articles, but rather to test their contributions to the synthesis and to identify their potential limitations (Bennion, Shaw, & Gibson, 2012;Malpass et al, 2009). …”
Section: Critical Appraisalmentioning
confidence: 99%
“…Concurring with reported high levels of treatment compliance 23 participants of this study continued with the treatment even when experiences of pain or discomfort were reported, illuminating a deep association between compliance and fear of blindness. 16,26 A fear of blindness Living with neovascular ARMD: the patient's story C McCloud and S Lake was pervasive in this study population, and more than one participant felt that death would be preferable to living with the limitations of blindness, which was a finding that resonated with suicide ideation following vision loss described by Casten and Rovner in 2008. 18 Ongoing lifestyle limitations described by the participants of this study were similar to findings of other studies of people with significant vision loss.…”
Section: Discussionmentioning
confidence: 78%
“…In the past qualitative explorations of people's experience of ARMD, generally reported on people with end-stage ARMD, often after significant vision has been lost. 16,17,18 Such studies predated the widespread use of anti-VEGF treatments for neovascular ARMD and were unable to elucidate experiences of people for whom vision loss could be avoided or limited.…”
Section: Introductionmentioning
confidence: 99%